"Kru Police D.A.R.E." Factor of Closely Relationship with Police For Participation on Crime Prevention Against to Students - Attano, Pol. Lt. Col. Dr. Kwanchai; Phaladech, Acting Lt. Dr. Janrob (Journal for Developing the Social and Community, 2018)
Drug Abuse Resistance Education project of Thailand (D.A.R.E. Thailand) aims to provide the basic knowledges to students on the danger of drugs and how to avoid drugs temptations, including 4 decision making patterns of D.A.R.E as follows: D (Define problems) A (Assess alternatives) R (Respond to decision-making) and E (Evaluate results), teaching by police officers called "Kru Police D.A.R.E.". This is a good relationship between police officers, students, teachers, parents and community members, that is consistent with the factor of the closely relationship with the police, related to the people participation on crime prevention. D.A.R.E. Thailand is only the curriculum for 5th or 6th Grade students but the youth in higher education, who are recklessly and curiosity, are also a risk of crimes. The guidelines to strengthen the knowledge for youth in higher education about the effects of crimes by creating skills and methods of decision making is creating the relationship between police officers and youth in higher education. This will result in confidence and cooperation on crime prevention.